HMGB1 released from dead tumor cells after insufficient radiofrequency ablation promotes progression of HCC residual tumor via ERK1/2 pathway. (31st December 2023) - Zhou, Yingshi; Liu, Xiaodi; Zhang, Wenyue; Xu, Yanni; Zhang, Qi; Xiong, Shiyu; Tang, Haifeng; Luo, Baoming
Abstract: Background: Radiofrequency ablation (RFA) is a first-line treatment for early-stage hepatocellular carcinoma (HCC). However, the recurrence after RFA remains an urgent challenge. Current studies have shown that residual tumor after RFA is an important cause of recurrence. Objective: We hypothesized that the products of dead tumor cells after RFA have direct effects on the development of residual tumors. Further, we investigated the underlying mechanisms. Methods: The proliferation and invasion ability of HepG2 and Huh7 cells were assessed using CCK-8, colony formation, EdU, transwell invasion and migration assay. Immunofluorescence and western blotting were used to show HMGB1 released from dead tumor cells. The levels of MMP2, MMP9, CyclinE1 and pERK1/2 were determined using western blotting. Finally, in vivo validation was performed in BALB/c nude mice xenograft tumor models. Results: The products of dead tumor cells after thermal treatment can promote the proliferation and invasion of residual HCC cells. Dead tumor cells could release high-mobility group box 1 (HMGB1) after thermal treatment. Similar to the products of dead tumor cells, the recombinant protein of HMGB1 can promote the proliferation and invasion of residual HCC cells. Moreover, HMGB1 could bind to receptor of advanced glycation end-products. Then, it activated the ERK1/2 pathway and significantly upregulated the expressions of MMP2, MMP9, and CyclinE1. Conclusion: Our study reveals that HMGB1 released by dead tumor cells after thermal treatment can promote the proliferation and invasion of residual HCC cells. Hence, the HMGB1/RAGE/ERK1/2 pathway is a potential target for improving the prognosis of HCC after radiofrequency ablation.